2020
DOI: 10.1016/j.heliyon.2020.e04556
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of targeted microalgae species growth using aquaculture sludge extracts

Abstract: Natural growth-promoting nutrients extracted from aquaculture sludge waste can be used to maximise microalgal growth. This study identified the influence of aquaculture sludge extract (SE) on four microalgae species. Conway or Bold's Basal Media (BBM) was supplemented with SE collected from a Sabak Bernam shrimp pond (SB) and Kota Puteri fish pond (KP), and tested using a novel microplate-incubation technique. Five different autoclave extraction treatment parameters were assessed for both collected SE, i.e., 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…[ 23 ] reported that C. vulgaris showed higher nitrogen requirements for growth. Study by [ 24 ] reported that modified soil extract from sludge pond did influence microalgae growth C. vulagaris and N. oceanica compared to the control. Although results were presented using optical density, correlation between optical density and number of cells is presented in Figure S1 (Supplementary S1) .…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] reported that C. vulgaris showed higher nitrogen requirements for growth. Study by [ 24 ] reported that modified soil extract from sludge pond did influence microalgae growth C. vulagaris and N. oceanica compared to the control. Although results were presented using optical density, correlation between optical density and number of cells is presented in Figure S1 (Supplementary S1) .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows light intensity limitation, part of the terms in Equation (11). The SE and temperature are fixed at 2 mL and 25°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The microplate-incubation technique 11 was conducted for the microalgae at 5 different SE volumes and concentration; 1, 2, 3, 6, and 10 mL, with the percentage (%) of 0%, 0.5%, 1%, 1.5%, 3%, and 5%, respectively. Media without SE was used as the control media in another microplate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations